2023
DOI: 10.1039/d2nr06607f
|View full text |Cite
|
Sign up to set email alerts
|

In situ self-exsolved ultrasmall Fe2P quantum dots from attapulgite nanofibers as superior cocatalysts for solar hydrogen evolution

Abstract: Ultrasmall Fe2P quantum dots (Fe2P QDs) are in situ self-exsolved from attapulgite (ATP) nanofibers by a low-temperature phosphidation method and the resulting Fe2P QDs/ATP has been shown to be an active, durable, and versatile H2 evolution cocatalyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 55 publications
(85 reference statements)
1
4
0
Order By: Relevance
“…2c) and many tiny dark dots with an average size of <5 nm are observed on the surface. The distance between the adjacent lattice fringes on a single dark dot is found to be 0.206 nm, consistent with the (201) planes of hexagonal Fe 2 P. 38 Moreover, the HAADF-STEM image and the corresponding EDS elemental mapping (Fig. 2d) of Fe 2 P/CGS indicate that although the distribution of Si, Al, and O elements is still homogeneous, the distribution of Fe is concentrated on the surfaces of CGS and mainly overlaps with the distribution of the P element, further confirming the formation of Fe 2 P particles.…”
Section: Resultssupporting
confidence: 68%
See 3 more Smart Citations
“…2c) and many tiny dark dots with an average size of <5 nm are observed on the surface. The distance between the adjacent lattice fringes on a single dark dot is found to be 0.206 nm, consistent with the (201) planes of hexagonal Fe 2 P. 38 Moreover, the HAADF-STEM image and the corresponding EDS elemental mapping (Fig. 2d) of Fe 2 P/CGS indicate that although the distribution of Si, Al, and O elements is still homogeneous, the distribution of Fe is concentrated on the surfaces of CGS and mainly overlaps with the distribution of the P element, further confirming the formation of Fe 2 P particles.…”
Section: Resultssupporting
confidence: 68%
“…More importantly, in comparison with CGS, a new peak corresponding to Fe–P species occurs in the resulting Fe 2 P/CGS and the content of FeO increases as a result of partial phosphidation of Fe 2 O 3 and FeOOH. 38,43 Moreover, as evidenced by the P 2p XPS spectra in Fig. 3b, additional doublet peaks due to the formation of Fe–P species appear in the P 2p spectrum of Fe 2 P/CGS as compared to the P 2p spectrum of the CGS.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…12 Attapulgite (ATP) is a natural iron-bearing mineral with a unique one-dimensional porous structure, excellent adsorption capacity and large number of active sites. 13 Previous studies have shown that Fe modification of ATP generates a large number of iron active sites, enabling adsorption and activation of nitrogen. 14 Furthermore, Fe-modified ATP exhibits an intrinsic crystal structure with a reduced band gap, which significantly enhances the photocatalytic performance.…”
Section: Introductionmentioning
confidence: 99%